Incorporating Task Based Language Learning Approach into a Kurdish Young EFL Learners' Classroom through Storytelling Technique in a Basic School in Kurdistan Region - Hamamorad, Atta (European Journal of Multidisciplinary Studies, 2018)
Effective teaching of English language to EFL learners has always been an important issue. There has been continuous efforts to find and adapt teaching methods and styles which suit learners' context, needs, and interest. This paper tries to devise a lesson for Kurdish young learners of grade six in a primary school in Kurdistan Region through integrating Task Based Learning aspects with the characteristics of Storytelling Method. Efficacious language learning approaches prioritise enhancing learners’ communicative performance over teaching complex grammatical structures in the early stage of learning a foreign language. Similarly, Task Based Language Learning approach aims to develop learners’ communicative competence via engaging them in authentic language activities and tasks. Storytelling technique on the other hand, can create an energetic, friendly ambiance in which learners are enthusiastically immersed in the lesson. They speak more confidently and are less afraid of making mistakes. The technique adapted, is new and novel in Kurdistan region's basic schools however, it falls within the scope of Communicative Teaching Approach which has recently become the popular approach for teaching English Language in basic schools of the region in the last few years.
Keywords: young learners, task based language learning, storytelling, task cycle